Survey of Knowledge, Attitudes and Practices of Brazilian Dentists Regarding Silver Diamine Fluoride - Ana Lúcia Vollú; Jessica Pronestino de Lima Moreira; Ronir Raggio Luiz; Fernanda Barja-Fidalgo; Andrea Fonseca-Gonçalves (Association of Support to Oral Health Research (APESB), 2022)
Objective: Current acceptability, barriers to use, and clinical/teaching practices of Silver Diamine Fluoride (SDF) among Brazilian dentists were investigated. Material and Methods: A Google forms questionnaire was sent to dentists (n=10,500) to collect information about the use of SDF and the dentists' workplace, experience, specialty, and city of practice. A logistic regression model was performed. Results: From 409 respondents, 13.2% used SDF. Working at universities increased the use of SDF by 2.29 times (p=0.018) compared to private offices. Each training year, the chance of SDF usage increased by 3%  (p=0.008). Pediatric dentists are more likely to use SDF (OR=6.76, p<0.001). There is no association between SDF usage and the city of practice. The majority (75.9%) indicated SDF for noncompliant patients. Dentists (75.9%) reported the exclusive use in deciduous teeth, while 24.1% also use in permanent teeth. The main barrier for non-users was a lack of knowledge (58.3%), while for users, tooth staining (90.7%) and parental acceptance (64.8%) were the complaints. Conclusion: The Silver Diamine Fluoride is not a common product used by the dentists from RJ. Its clinical applicability should be further disseminated; thus, lack of scientific knowledge would cease to be a problem in the use of SDF to arrest caries lesions.